The vertebral syndrome in various types of mucopolysaccharidosis: clinical features and treatment - Sergey O. Ryabykh; Polina V. Ochirova; Alexandr V. Gubin; Sergey V. Kolesov; Dmitry A. Kolbovsky; Anastasia N. Tretjakova; Tatyana V. Ryabykh; Svetlana N. Medvedeva; Dmitry M. Savin; Akeksandr V. Burtsev; Marat S. Saifutdinov (Хирургия позвоночника, 2019)
The paper presents recommendations on the assessment and treatment of vertebral pathology in patients with various types of mucopoly- saccharidosis. The recommendations are based on literature data and the authors’ own experience. The purpose of the publication is an invitation to the discussion in the format of an expert consensus.